Association between opium use and bladder cancer: A case-control study in a high risk area of Iran - Hamideh Rashidian; Ali Akbar Haghdoost; Maryam Hadji; Maryam Marzban; Mahin Gholipour; Kazem Zendehdel (Clinical Epidemiology and Global Health, 2021)
Background: Bladder cancer is one of the common cancers. Currently some studies found an association between opium use and incidence of bladder cancer, however, underreporting and detection bias was high in the previous studies and also some of them did not adjust their results for confounding variables and had small sample size, various and unclear definition of opium use, and lack of data on starting age, duration, dose, and route of opium consumption. In this study we investigated the association between opium use and incidence of bladder cancer, overcoming previous studies limitations and doing sensitivity analyses for underreporting bias. Methods: We performed a population-based case–control study, including 300 cases diagnosed with bladder cancer and 600 controls (matched for age, sex, and place of residence) between 2013–2015. We used conditional logistic regression models to estimate odds ratios (OR) and 95% confidence intervals (CI). Results: Overall, 200 cases (64.9%) and 172 controls (27.9%) reported regular use of opium, resulting in an adjusted OR (95% CI) of 4.4 (2.9–6.5). Dose response relationship was seen and the adjusted OR for low and high dose consumption groups were 4.2 (95% CI 2.6-6.8) and 4.5 (95% CI 2.9-7.2) respectively. The association between opium use and bladder cancer was statistically significant even after controlling for underreporting bias. Conclusion: This study confirmed that opium use was associated with the bladder cancer incidence. We suggest primary prevention and early detection for bladder cancer, especially in the high risk groups.